Dilated cardiomyopathy and arrhythmogenic left ventricular cardiomyopathy: a comprehensive genotype-imaging phenotype study. (16th July 2019) - Augusto, João B; Eiros, Rocio; Nakou, Eleni; Moura-Ferreira, Sara; Treibel, Thomas A; Captur, Gabriella; Akhtar, Mohammed M; Protonotarios, Alexandros; Gossios, Thomas D; Savvatis, Konstantinos; Syrris, Petros; Mohiddin, Saidi; et al.
Abstract: Aims : Myocardial scar detected by cardiovascular magnetic resonance has been associated with sudden cardiac death in dilated cardiomyopathy (DCM). Certain genetic causes of DCM may cause a malignant arrhythmogenic phenotype. The concepts of arrhythmogenic left ventricular (LV) cardiomyopathy (ALVC) and arrhythmogenic DCM are currently ill-defined. We hypothesized that a distinctive imaging phenotype defines ALVC. Methods and results : Eighty-nine patients with DCM-associated mutations [desmoplakin ( DSP ) n = 25, filamin C ( FLNC ) n = 7, titin n = 30, lamin A/C n = 12, bcl2-associated athanogene 3 n = 3, RNA binding motif protein 20 n = 3, cardiac sodium channel NAv 1.5 n = 2, and sarcomeric genes n = 7] were comprehensively phenotyped. Clustering analysis resulted in two groups: ' DSP/FLNC genotypes' and 'non- DSP/FLNC '. There were no significant differences in age, sex, symptoms, baseline electrocardiography, arrhythmia burden, or ventricular volumes between the two groups. Subepicardial LV late gadolinium enhancement with ring-like pattern (at least three contiguous segments in the same short-axis slice) was observed in 78.1% of DSP/FLNC genotypes but was absent in the other DCM genotypes ( P < 0.001). Left ventricular ejection fraction (LVEF) and global longitudinal strain were lower in other DCM genotypes ( P = 0.053 and P = 0.015, respectively), but LV regional wall motion abnormalities were more common in DSP/FLNC genotypes ( P < 0.001). DSP/FLNC patients with non-sustained ventricular tachycardia (NSVT) had more LV scar ( P = 0.010), whereas other DCM genotypes patients with NSVT had lower LVEF ( P = 0.001) than patients without NSVT. Conclusion: DSP/FLNC genotypes cause more regionality in LV impairment. The most defining characteristic is a subepicardial ring-like scar pattern in DSP/FLNC, which should be considered in future diagnostic criteria for ALVC.